Pengaruh Stress Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja di PT. Amos Indah Indonesia - Agnia Asyifa; Ignatius Ario Sumbogo (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of work stress and work discipline on work productivity at PT. Amos Indah Indonesia. This study uses quantitative methods with non-probability sampling techniques with purposive sampling method. Distributing the questionnaire as many as 197 respondents were employees at PT.Amos Indah Indonesia who had met several criteria. This study uses hypothesis testing and multiple linear regression tests that are processed using the SPSS v.25 program. The results showed that, Work Stress and Work Discipline had a significant effect on Work Productivity, either partially or simultaneously.